1990
DOI: 10.1017/s0022112090003226
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surfactants on drop deformation and breakup

Abstract: The effects of surface-active agents on drop deformation and breakup in extensional flows at low Reynolds numbers are described. In this free-boundary problem, determination of the interfacial velocity requires knowledge of the distribution of surfactant, which, in turn, requires knowledge of the interfacial velocity field. We account for this explicit coupling of the unknown drop shape and the evolving surfactant distribution. An analytical result valid for nearly spherical distortions is presented first. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
333
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(360 citation statements)
references
References 36 publications
20
333
2
Order By: Relevance
“…7. Our results in supercritical flow resemble the results obtained by Li and Pozrikidis 15 and Stone and Leal 16 in subcritical flows. For Peϭ0, the droplet deformation decreases with increasing ‫,*⌫ץ/*ץ‬ i.e., with increasing ␤.…”
Section: Influence Of ٢õ٢⌫ For Constant Concentrationsupporting
confidence: 91%
See 1 more Smart Citation
“…7. Our results in supercritical flow resemble the results obtained by Li and Pozrikidis 15 and Stone and Leal 16 in subcritical flows. For Peϭ0, the droplet deformation decreases with increasing ‫,*⌫ץ/*ץ‬ i.e., with increasing ␤.…”
Section: Influence Of ٢õ٢⌫ For Constant Concentrationsupporting
confidence: 91%
“…In such a case where the Marangoni stresses are large, the droplet deformation becomes dilution dominated and the droplet deforms less than an equivalent clean droplet. 10,[13][14][15][16] For higher viscosity ratio droplets, the convection is small compared to the diffusion ͑low Pe͒ and the surfactant is more uniformly distributed. 8 Therefore, the effect of surfactant is smaller for higher viscosity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling this process is not trivial since a detailed model for the problem involves simultaneous solutions of the Stokes equations in each liquid together with velocity and stress boundary conditions at the interface. [25][26][27][28] The normal and shear stress boundary conditions couple the velocity field with variations in the surface tension along the interface, and additional equations are also needed in order to couple surface tension with surface concentration, and surface concentration with diffusion, adsorption, and desorption processes for mass transfer of molecules from the bulk onto the interface.…”
Section: A Simplified Modelmentioning
confidence: 99%
“…These numerics are based upon a boundary integral formulation that was extended to include surfactant dynamics by Stone and Leal 26 and Milliken et al 27 While Eggleton and co-workers focused on elongational flow, recent work by Bazhlekov et al 28 using similar numerical methods has also shown similar behavior in droplets subject to shearing flows, also using insoluble surfactants. It is worth noting that this recent work reproduces numerically an experimental result reported by Grace 29 showing that below a critical viscosity ratio, surfactants lead to a sharp reduction in the critical capillary number for breakup of sheared droplets, and that this critical capillary number is independent of viscosity ratio below the critical value.…”
Section: Introduction and Background On Tipstreamingmentioning
confidence: 99%
“…Normalizing velocities by U = (ρ w − ρ nw )gR 2 /µ w and length scales by the average pore radius R, the stress jump associated with surface tension at the interface between the two fluids becomes (Stone & Leal 1990;Pozrikidis 1992;Manga & Stone 1993) 11) where the superscript * refers to a dimensionless variable, x is located at the interface between the two fluids, n is the outward normal to the interface, ∇ s is the gradient along the interface, Bo = ρgR 2 /γ is the Bond number and λ = µ nw /µ w . Finally, we solve for the conservation of enthalpy for the three phases…”
mentioning
confidence: 99%